microRNAs: An opportunity to overcome significant challenges in malaria detection and control - Ruhi Sikka; Praveen Kumar Bharti; Himanshu Gupta (Elsevier, 2022)
Organ damage and pathological disease states lead to the rapid release of microRNAs (miRNAs), a class of endogenous small non-coding RNAs, into the blood circulation. Because secreted miRNAs can be detected in biologic fluids such as plasma, they are currently being explored as promising non-invasive biomarkers of infectious and non-infectious diseases. Malaria remains a major global health challenge but still the potential of miRNAs has not been explored extensively in the context of malaria compared to other diseases. Here, we highlight important miRNAs found during different phases of the malaria life cycle in the anopheline vector and the human host. We have also put forward our opinion on how malaria parasite-stage-specific miRNAs can be incorporated into new diagnostic and prognostic tools to detect carrier mosquitoes and infected patients. In addition, we have emphasised the potential of miRNAs to be used as new therapeutics to treat severe malaria patients, an unresearched area of malaria control.